Intellectual Property Ownership of AI-Generated Content - A. Kirakosyan (Цифровое право, 2024)
Until recently, intellectual creativity was considered as an exclusively human phenomenon and intellectual property legislation was built on the basis of motivating and enhancing human inventiveness. This self-evident assumption is being challenged due to the development of artificial intelligence technologies in the recent decades. In this article author analyzes some aspects of intellectual property law development, including the possibility of recognizing an artificial intelligence as a creator of intellectual activity results. The author examines the legal status of artificial intelligence under Armenian law and foreign intellectual property legislation, analyzes existing approaches to the legal regime and intellectual property ownership of objects created with the help of artificial intelligence. The paper aims to determine the proper right holder to content generated by artificial intelligence and formulate some policy prospects of artificial intelligence regulation. The methodological basis of the research includes general scientific and special legal methods. The author places particular emphasis on the dogmatic (doctrinal) research methods, which made it possible to analyze existing approaches to protection of intellectual property rights. The research is also based on the comparative legal method and analytical legal method of commenting current law of Armenia and foreign countries. The results of the study allow author to substantiate that the actual right holder to the content produced by the neural network is the programmer of the underlying algorithm system. The author concludes that the construction of a solid legislative system should be carried out taking into account the specifics of the areas of application of artificial intelligence, ensuring a balance between the interests of individuals, society and the state related to the development of innovative technology.